2010
DOI: 10.1051/0004-6361/201014356
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic confirmation of a galaxy cluster associated with 7C 1756+6520 atz= 1.416

Abstract: We present spectroscopic follow-up of an overdensity of galaxies photometrically selected to be at 1.4 < z < 2.5 found in the vicinity of the radio galaxy 7C 1756+6520 at z = 1.4156. Using the DEIMOS optical multi-object spectrograph on the Keck 2 telescope, we observed a total of 129 BzK-selected sources, comprising 82 blue, star-forming galaxy candidates (sBzK) and 47 red, passivelyevolving galaxy candidates (pBzK*), as well as 11 mid-infrared selected AGN candidates. We obtain robust spectroscopic redshifts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…These environments are highly likely to be proto-clusters or clusters, several of which have already been confirmed (Venemans et al 2007;Galametz et al 2010;Hatch et al 2011b;Galametz et al 2013). However, Fig.…”
Section: Heating the Intracluster Mediummentioning
confidence: 65%
“…These environments are highly likely to be proto-clusters or clusters, several of which have already been confirmed (Venemans et al 2007;Galametz et al 2010;Hatch et al 2011b;Galametz et al 2013). However, Fig.…”
Section: Heating the Intracluster Mediummentioning
confidence: 65%
“…De presented the Spitzer/IRAC follow-up of a sample of 70 radio galaxies and found that at least four have companions within 6 with mid-infrared colours consistent with AGN. The spectroscopic follow-up of one of them, 7C 1756-152 at z = 1.42, showed a companion AGN, offset by 6 from the radio galaxy (Galametz et al 2010b).…”
Section: The Radio Galaxy Companionsmentioning
confidence: 96%
“…Complementary studies have attempted to reveal the massive evolved population in these galaxy structures at z ≥ 2 (e.g., Kajisawa et al 2006;Tanaka et al 2007;Zirm et al 2008;Galametz et al 2009aGalametz et al , 2010b in order to determine the epoch of appearance of the first red sequence galaxies. However, most of these confirmed galaxy structures at z ≥ 2 are still in the act of collapsing i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed the sensitivity required to detect L å galaxies at z∼0.7 with mid-infrared observations, which Spitzer reaches in <2 minute integrations, is sufficient to detect such galaxies to z2. Several large projects are exploiting mid-infrared data to search for high-redshift galaxy clusters using Spitzer and WISE (e.g., Eisenhardt et al 2008;Galametz et al 2010Galametz et al , 2013Papovich et al 2010;Stanford et al 2012Stanford et al , 2014Muzzin et al 2013;Rettura et al 2014;Wylezalek et al 2014;Brodwin et al 2015Brodwin et al , 2016PaternoMahler et al 2017). Such work has, for example, proved useful for (i) measuring the galaxy cluster autocorrelation function out to z∼1.5, which provides a measure of the typical galaxy cluster mass (Brodwin et al 2007); (ii) targeted cosmological surveys for z>1 SNe Ia in dust-free environments (Suzuki et al 2012); (iii) probing evolution in the σ-T x correlation (Brodwin et al 2011); (iv) using the rest-frame near-infrared luminosity function and rest-frame optical colors to probe the formation epoch of cluster galaxies (Mancone et al 2010Snyder et al 2012;Wylezalek et al 2014;Cooke et al 2015; Nantais et al 2016); (v) probing the role of AGN feedback in forming clusters (Galametz et al 2009;Martini et al 2013); (vi) leading cosmological investigations based on the incidence of massive, high-redshift clusters Gonzalez et al 2012);and (vii) probing the dependency of galaxy quenching on environment (Muzzin et al 2014, Nantais et al 2017.…”
Section: Introductionmentioning
confidence: 99%